AB0536 Renal Biopsy in Patients with Systemic Lupus Erythematosus and Proteinuria Less than 0.5 G/24Hrs. (10th June 2014) - Ricse, M.; Narváez, J.; Albert, G.; Estrada, P.; Armengol, E.; Giménez, C.; Roset, A.; De Lama, E.; Torras, J.; Rodríguez, J.; Mitjavila, F.; Nolla, J.M.
Abstract : Background: The currently indications for a first renal biopsy in patients with systemic lupus erythematosus (SLE) are the presence of a confirmed 24 hours urinary proteins ≥0.5 g, an active urinary sediment (microhematuria/buffy/casts) or an unexplained deterioration of renal function. The performance of renal biopsies in patients with proteinuria below 0.5 g/day and inactive sediment or with minimal alterations, is still in discussion. However, current knowledges of the existence of silent lupus nephritis have reopened the debate on the need to perform biopsies with the purpose of evidencing minimal renal disease, in SLE and basic activity disease. Objectives: To review the histological findings in patients with SLE and urinary proteins lower than 0.5 g in 24 Hours. Methods: We have included 243 patients with SLE, all attended in a Tertiary University Hospital without pediatric population assigned, between 1980 and 2013. They have been recorded in a specific database (ACHILLES record). Were selected patients without renal failure who underwent renal biopsy because they presented proteinuria <0.5 g/24 hours of recent onset (present in 2 consecutive samples) with active urinary sediment. Results: Six patients were identified, all with SLE immunologically active. The biopsy was performed for presenting, along with proteinuria, an active urinary sediment with pyuria and/or intermittent or persistent microscopic hematuria, but with evidence of more than 80% dysmorphic RBCs suggesting glomerular origin. In 5 of the 6 patients, renal biopsy demonstrated the existence of lupus nephritis. In the remaining patient, biopsy identified the presence of thrombotic microangiopathy as a result of a secondary antiphospholipid syndrome. The main clinical and histological data are showed in the following table. Conclusions: In patients with active SLE, histological findings compatible with lupus nephritis can be seen even with less than 0.5 g/24 hours urinary proteins (including the presence of severe histological classes in a high percentage of patients). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5662